Perfusion imaging and recurrent cerebrovascular events in intracranial atherosclerotic disease or carotid occlusion. Issue 6 (August 2018) - Sacchetti, Daniel C; Cutting, Shawna M; McTaggart, Ryan A; Chang, Andrew D; Hemendinger, Morgan; Mac Grory, Brian; Siket, Matthew S; Burton, Tina; Thompson, Bradford; Rostanski, Sara K; Prabhakaran, Shyam; Willey, Joshua Z; et al.
Background: Large vessel disease stroke subtype carries the highest risk of early recurrent stroke. In this study we aim to look at the association between impaired perfusion and early stroke recurrence in patients with intracranial atherosclerotic disease or total cervical carotid occlusion. Methods: This is a retrospective study from a comprehensive stroke center where we included consecutive patients 18 years or older with intracranial atherosclerotic disease or total cervical carotid occlusion admitted with a diagnosis of ischemic stroke within 24 h from symptom onset with National Institute Health Stroke Scale < 15, between 1 December 2016 and 30 June 2017. Patients with (1) evidence of ≥ 50% stenosis of a large intracranial artery or total carotid artery occlusion, (2) symptoms referable to the territory of the affected artery, and (3) perfusion imaging data using the RAPID processing software were included. The primary predictor was unfavorable perfusion imaging defined as Tmax > 6 s mismatch volume (penumbra volume–infarct volume) of 15 ml or more. The outcome was recurrent cerebrovascular events at 90 days defined as worsening or new neurological symptoms in the absence of a nonvascular cause attributable to the decline, or new infarct or infarct extension in the territory of the affected artery. We used Cox proportional hazards models to determine the association between impaired perfusion and recurrent cerebrovascular events. Results: Sixty-two patients met our inclusion criteria; mean age 66.4 ± 13.1 years, 64.5% male (40/62) and 50.0% (31/62) with intracranial atherosclerotic disease. When compared to patients with favorable perfusion pattern, patients with unfavorable perfusion pattern were more likely to have recurrent cerebrovascular events (55.6% (10/18) versus 9.1% (4/44), p < 0.001). This association persisted after adjusting for potential confounders (adjusted hazard ratio 10.44, 95% confidence interval 2.30–47.42, p = 0.002). Conclusion: Perfusion mismatch predicts recurrent cerebrovascular events in patients with ischemic stroke due to intracranial atherosclerotic disease or total cervical carotid occlusion. Studies are needed to determine the utility of revascularization strategies in this patient population.